Embodying Black Religions in Africa and Its Diasporas (Duke University Press, 2022)
The contributors to Embodying Black Religions in Africa and Its Diasporas investigate the complex intersections between the body, religious expression, and the construction and transformation of social relationships and political and economic power. Among other topics, the essays examine the dynamics of religious and racial identity among Brazilian Neo-Pentecostals; the significance of cloth coverings in Islamic practice in northern Nigeria; the ethics of socially engaged hip-hop lyrics by Black Muslim artists in Britain; ritual dance performances among Mama Tchamba devotees in Togo; and how Ifá practitioners from Mexico, Colombia, Venezuela, Trinidad, and the United States join together in a shared spiritual ethnicity. From possession and spirit-induced trembling to dance, the contributors outline how embodied religious practices are central to expressing and shaping interiority and spiritual lives, national and ethnic belonging, ways of knowing and techniques of healing, and sexual and gender politics. In this way, the body is a crucial site of religiously motivated social action for people of African descent. Contributors. Rachel Cantave, Youssef Carter, N. Fadeke Castor, Yolanda Covington-Ward, Casey Golomski, Elyan Jeanine Hill, Nathanael J. Homewood, Jeanette S. Jouili, Bertin M. Louis Jr., Camee Maddox-Wingfield, Aaron Montoya, Jacob K. Olupona, Elisha P. Renne